Two-dimensional chlodowsky variant of q-Bernstein-schurer-stancu operators - Özarslan, Mehmet Ali; Vedi, Tuba (Eudoxus Press, LLC, 2017)
In this paper, two-dimensional Chlodowsky variant g-based Bernstein-Schurer-Stancu operators are introduced. Korovkin-type approximation theorems in different function spaces are studied. The error of approximation by using full modulus of continuity and partial modulus of continuities are given. Moreover, we introduce a generalization of our operators and investigate its approximation in more general weighted space. © 2017 by Eudoxus Press, LLC,LLC,All rights reserved.
Keywords: Chlodowsky operators; Chlodowsky variant of q-Bernstein-schurer-stancu operators; Modulus of continuity; q-Bernstein operators; Weighted space